PERENCANAAN GEDUNG RAWAT INAP RS MM DUNDA MENGUNAKAN SOFTWARE SAP 2000 - Nento, Sartan; Otto, Abdul Rajab; Olii, Muh Ramdhan; Olii, Aleks; Doda, Nurhayati (Universitas Bina Taruna Gorontalo, 2023)
This research aims to analyze the structural analysis of a building using software Since computerization is used to complete every building plan or design, the development of technology and information, especially computerization in the world of construction, cannot be separated anymore and is not a new phenomenon. The decision to use a computer to complete construction plans was based on the fact that computers have the advantage of not only being able to finish quickly but also having accuracy, effectiveness, and ease of use (Dwi Deshariyanto, Anita Intan Nura Diana 2021). The following findings have been achieved based on the final results of the development of this final report. using the SAP 2000 version 22 program to calculate reinforcement in columns, beams, and floor slabs, Using earthquake response spectrum design analysis, earthquake load calculations refer to SNI 1726: 2019 (Procedures for Planning Earthquake Resistance for Buildings and Non-Buildings), The design of this building is based on the type of reinforced concrete structure and the Unique Moment Resisting Frame System (SRPMK). The floor difference is in accordance with the relevant SNI criteria